Stabilizers Effects Comprehensive Assessment on the Physical and Chemical Properties of Soft Clays - Farzad Pourebrahim; Sayyed Yaghoub Zolfegharifar (Shock and Vibration)
Deep soil mixing (DSM) is one of the practical methods of soil improvement in the world, which produces cement columns and modification by injecting stabilizing materials such as cement or lime using a mechanically hollow shaft drill in the soil. In this method, the soil characteristics are improved by mixing the soil with cementitious materials by deep mixers and creating cement soil columns. In addition, by overlapping the columns before full setting, continuous walls can be constructed below the ground. The aim of this study was to investigate the effect of the additive type on the strength of the samples. For soil samples stabilized with lime, the maximum value of uniaxial resistance was 247 kPa and for the mixture of 10% lime and 4% sodium silicate was obtained.